Investigating the Causes of Work-Related Injuries and their Impact on the Employee Health and Safety in Organizations in GCC Region - Solanki, Kalpana (Advances in Social Sciences Research Journal, 2024)
Ensuring employee health and safety has been considered the top priority by OSHA. Although employee health and safety has an been considered paramount in ensuring effective company operations around the world yet limited efforts are being taken by the organizations to enhance employee health and safety. This research paper aims to explore the various industrial hazards and their impact on the employee health and safety in the GCC region. This research uses primary and secondary data, Qualitative and quantitative data analysis techniques to test the hypothesis. Descriptive statistics including relationship charts, frequency analysis, and ANOVA testing were included to reach the conclusion. The response was received 100 responses from different industries in GCC region to whom the survey was disseminated. The researcher has also used open publicly available data through the published information by the General Organization for Social Insurance (GOSI). The results conclude close inverse relationship between the dependent and independent variables where the (Independent variable) is Employee safety and health and the dependent variables are electric hazard, fire hazards, fall hazards, ergonomics hazards. The reduction in the hazards will lead to increase in the employee safety and health.